THE PHYSICAL FITNESS OF SCHOOLCHILDREN OF THE PRIMARY EDUCATION IN MOSSORO/RN CITY (Fiep Bulletin - online, 2014)
Summary: Physical fitness is the ability to perform muscular work in a pleasurable way, encompassing strength, muscular endurance, flexibility, body composition and cardio respiratory fitness. The purpose of this descriptive study was to evaluate the physical fitness of 50 children of both sexes aged 9-11 years enrolled in the 4th and 5th year of elementary school SESC City Mossley / RN. As an evaluation tool , the motor tests (flexibility , agility , abdominal strength and speed) and PROESP to check the weight and height was used anthropometric scale digital brand Welmy and Sanny stadiometer , with these measures was obtained Index Body Mass Index (BMI ) . All tests were compared with the reference data of PROESP. For statistical analysis we used the SPSS software version 20.0 Portuguese, the normality of the data was checked with the Shapiro Wilk test , with a confidence level of p > 0.05 . For nonparametric variables used - the Man Whitney test. The analyzed data allow us to conclude that most of the students showed a satisfactory result considering the body mass index regarding fitness concluded that the majority of students is evaluated at very low level and weak. It is recommended that well beyond the planning of physical education classes in school and practice, students should adopt healthy behaviors in their day - to-day efforts to improve the quality of life.
Keywords: Physical Fitness; School; school .